Assessing Water-Provision of Population in the System of Measures Aimed at Bottled Drinking Water Production - A. D. Kalach (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies issues of providing the population with accessible drinking water of high quality. The author puts forward a new integral index to assess water-provision of people, which takes into account different factors, including accessibility of water resources, their quality, the level of water-supplying infrastructure and efficiency of water resource management. Integral index was elaborated with due regard to existing methods of water resource estimation, but it was extended and now it includes additional parameters that are specific for conditions in the Russian Federation. For each Russian region a proposed index was calculated, which demonstrates regions with highest and lowest provision with water. The obtained results showed serious regional differences in the level of water provision, which proves the necessity of targeted state policy and investment in water infrastructure, including such alternative methods as bottled water.